2019
DOI: 10.11622/smedj.2018105
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of ultrasonography-guided fine needle aspiration cytology and significance of non-diagnostic cytology in the preoperative detection of thyroid malignancy

Abstract: The accuracy of ultrasonography-guided FNAC at our institution was comparable to that reported in the literature. There appears to be very low probability of malignancy in sonographically benign nodules with initial non-diagnostic FNAC results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…In this study, solidity, hypoechogenicity, irregular margins, taller-than-wide shape, microcalcifications and posterior echo attenuation associated with malignant nodules, whereas regular halo associated with benign nodules. Furthermore, taller-than-wide shape, microcalcifications, hypoechogenicity and irregular margins were independent risk factors for malignancy, consistent with the results of previous studies ( 15 , 18 , 39 , 40 , 41 ). Taller-than-wide shape is a highly specific indicator of thyroid cancer, with studies reporting a specificity of 81.5–98.5% for malignant thyroid nodules with a taller-than-wide shape ( 15 , 23 , 42 ).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, solidity, hypoechogenicity, irregular margins, taller-than-wide shape, microcalcifications and posterior echo attenuation associated with malignant nodules, whereas regular halo associated with benign nodules. Furthermore, taller-than-wide shape, microcalcifications, hypoechogenicity and irregular margins were independent risk factors for malignancy, consistent with the results of previous studies ( 15 , 18 , 39 , 40 , 41 ). Taller-than-wide shape is a highly specific indicator of thyroid cancer, with studies reporting a specificity of 81.5–98.5% for malignant thyroid nodules with a taller-than-wide shape ( 15 , 23 , 42 ).…”
Section: Discussionsupporting
confidence: 91%
“…A study showed that the sensitivity, speci city, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of FNA were 96.9%, 81.7%, 73.8%, 98%, and 86.9%, respectively [36]. In the study of Chieng J et al, FNAC predicted malignancy with a sensitivity, speci city, PPV, NPV, false positive rate, false negative rate and total accuracy of 90.7%, 53.6%, 43.3%, 93.7%, 46.4%, 9.3% and 64.1%, respectively [37]. However, FNAC is considered to be "uninterpretable" in 10 to 20% of cases or simply "suspicious" in 9 to 38% of cases [38].In addition, it is currently estimated that cytologically indeterminate results are diagnosed in up to 25% to 30% of thyroid biopsies [39,40].Therefore, the use of molecular markers is important for improving diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 96%
“…The sensitivity of FNAC varies in literature between 55% and 95% and our value is on the lower end of the spectrum. [8,10,11,19,20] The variation exists due to the different methods of calculation of these variables in different studies. The discrepancy arises mostly in the categorizing of Bethesda 3 (AUS) and Bethesda 4 (follicular neoplasm) into benign or malignant categories.…”
Section: Discussionmentioning
confidence: 99%